Mediating role of access to finance and moderating role of business environment on the relationship between strategic orientation attributes and performance of small and medium enterprises in Nigeria - Aminu, Ibrahim Murtala (2015)
The main objective of this study is to examine the mediating role of access on finance and the moderating role of business environment on the relationship between entrepreneurial orientation (EO), market orientation (MO), learning orientation (LO), technology orientation (TO) and performance of Small and Medium Enterprises (SMEs) in Nigeria. Data were collected from the SMEs operating in North Western Nigeria using a cross-sectional study design. The study adopted cluster sampling and randomly selected 522 respondents and questionnaires were distributed and collected through the personally-administered method. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test the study hypotheses. This study finds that EO, LO and TO are important strategic orientations for the performance of SMEs in Nigeria. The findings reveal that SMEs’ access to finance depends on the degree of MO, LO and TO of the enterprise. It is expected EO would improve a firm’s accessibility to finance, but the finding of this study does not support this expectation as EO negatively influences firm performance. Interestingly, the results further show that with better access to finance, MO, LO and TO influence firm performance. Furthermore, business environment does not have a significant moderating influence on the paths between EO and performance, MO and performance, LO and performance and TO and performance. The results of this study provide important insights to owner-managers, policy-makers and researchers to further understand the effects of strategic orientations on firm performance. Owner-mangers of SMEs should emphasize on EO, MO, LO and TO; however, it is important to note that over-concentration on EO may result in lower accessibility of financing. Policy-makers should encourage SMEs to improve their cash flow, profit and retained earnings which may encourage financial institutions to provide them with financial services. Lastly, limitations of the current study and avenues for future research are discussed